A Retrospective Review of Orbital Decompression for Thyroid Orbitopathy with Endoscopic Preservation of the Inferomedial Orbital Bone Strut. Issue 5 (September 2017) - Finn, Avni P.; Bleier, Benjamin; Cestari, Dean M.; Kazlas, Melanie A.; Dagi, Linda R.; Lefebvre, Daniel R.; Yoon, Michael K.; Freitag, Suzanne K.
Abstract : Purpose: To determine incidence of new-onset diplopia, resolution of preexisting diplopia, and impact on proptosis resulting from endoscopic orbital decompression with and without preservation of the inferomedial orbital strut for thyroid orbitopathy. Methods: Retrospective review of all patients undergoing endoscopic 2- or 3-wall decompression with or without preservation of the strut for thyroid orbitopathy from January 2012 to June 2015. Results: Twenty-six patients (45 orbits) were included and divided into 4 primary categories: 2-wall decompression with strut preservation (4 orbits, 8%), 2-wall decompression with strut removal (7 orbits, 16%), 3-wall decompression with strut preservation (27 orbits, 60%), and 3-wall decompression with strut removal (7 orbits, 16%). The incidence of new-onset diplopia was 20% (2/10 patients without preoperative diplopia) overall and 16% in the strut preservation group (1/6 patients without preoperative diplopia). Resolution of diplopia occurred in 4 of 16 patients (25%) with preoperative diplopia, and all 4 had been treated with a 3-wall decompression with strut preservation. Resolution of diplopia in the group treated with strut preservation was 36% (4/11 patients with preoperative diplopia), and 0% of the 5 diplopic patients treated without strut preservation. Reduction in proptosis was statistically greater in those treated with strut removal ( p = 0.003). Conclusions: This study demonstrates that endoscopic orbital decompression with preservation of the inferomedial bone strut results in a comparable to lower rate of new-onset diplopia compared with other reported techniques. When combined with 3-wall balanced decompression, this technique demonstrates a high rate of resolution of preexisting diplopia. Abstract : Orbital decompression with preservation of the orbital strut for thyroid eye disease shows a comparable rate of new-onset diplopia to other techniques and a high rate of resolution of preoperative diplopia.